Characterization of Nanoparticles and Colloids in Aquatic Systems 1. Small Angle Neutron Scattering Investigations of Suwannee River Fulvic Acid Aggregates in Aqueous Solutions - Diallo, Mamadou S.; Glinka, Charles J.; Goddard, William A.; Johnson, James H. (Journal of nanoparticle research : an interdisciplinary forum for nanoscale science and technology, 2005)
Fulvic acids (FA) and humic acids (HA) constitute 30-50% of dissolved organic matter in natural aquatic systems. In aqueous solutions, a commonly accepted view is that FA and HA exist as soluble macroligands at low concentration and as supramolecular aggregates at higher concentration. The size, shape and structure of these aggregates are still the subject of ongoing debate in the environmental chemistry literature. In this article, we use small angle neutron scattering (SANS) to assess the effects of solute concentration, solution pH and background electrolyte (NaCl) concentration on the structures of Suwannee River FA (SRFA) aggregates in D^sub 2^O. The qualitative features of the SANS curves and data analysis are not consistent with the view point that SRFA forms micelle-like aggregates as its concentration in aqueous solution increases. We find that SRFA forms fractal aggregates in D^sub 2^0 with size greater than 242 nm. The SRFA aggregates undergo a significant degree of restructuring in compactness as solution pH, solute concentration and NaCl concentration increase.[PUBLICATION ABSTRACT]